"Starting with Derrida: Plato, Aristotle and Hegel" - "Gaston, Sean" (London, 2008)
How does one start with Derrida? In this exciting and accessible book, Sean Gaston presents a new kind of introduction to Jacquas Derrida, arguably the most important and influential European thinker of the last century. Derrida claimed that However old I am, I am on the threshold of reading Plato and Aristotle ... we need to read them again and again and again . In Starting with Derrida, Gaston introduces Derrida s major works and ideas by tracing Derrida s reading (and re-reading) of Plato, Aristotle and Hegel throughout his writings. Starting with Derrida argues for the importance of the relationship between philosophy, literature and history in Derrida s work and addresses key concepts in Derrida s thought, including his work on time and space, being and the soul, sensation and thought, history and literature, the concept and the name. The book encourages the reader to enter Derrida s varied and complex legacy through the moments in Derrida s work that are concerned with the question of origins and beginnings. By actively engaging with Derrida s ideas in this way, Gaston reveals a new and highly original reading of Derrida s work and provides a useful introduction to his entire corpus. This exciting new book is essential reading for students of Philosophy and literary theory and, indeed, anyone interested in the work of this hugely important thinker.
Keywords: "Derrida, Jacques"